Missed canal as a factor affecting the periapical status - M. Yu. Pokrovsky; O. A. Aleshina; T. P. Goryacheva (LLC "Endo Press", 2023)
Aim. To identify the relationship between the presence of a "missed" root canal and the periapical status.Materials and methods. 500 CBCT images of patients of both sexes were studied: 2915 teeth after endodontic treatment, of which 1549 were multicanal. Profile diagnostic criteria were used to identify the "missed" canal.Results. 518 "missed" root canals were revealed, which accounted for 33.4% of the number of multi-canal teeth. In 228 cases, changes in periapical tissues were noted, including 1 case of widening of periodontal ligament space, which accounted for 44% of the total number of "missed" canals. It was noted that the risk of developing apical periodontitis is higher for cases with "missed" canals (p < 0.001). The relationship between the untreated canal and the periapical status is statistically assessed as medium or relatively strong, which confirms the relevance of accurate diagnosis of the anatomy and topography of the root canal system at all stages and by all available methods.Conclusions. In case of sufficient duration of observation, absence of symptoms, absence of periapical changes (radiologically) - repeated treatment for the purpose of endodontic treatment of the "missed" root canal is not justified. If there are changes in the periapical tissues, repeated endodontic intervention should be performed. In this case, preference should be given to endodontic re-treatment using a microscope.